BEYOND THE DYAD: THE RELATIONSHIP BETWEEN PRESCHOOLERS' ATTACHMENT REPRESENTATIONS AND FAMILY TRIADIC INTERACTIONS. Issue 2 (6th March 2017) - C., Francisca Pérez; Moessner, Markus; A., María Pía Santelices
ABSTRACT: This study examines the relationship between triadic family interactions and preschoolers' attachment representations, or internal working models (IWMs), from a qualitative and dimensional perspective. Individual, relational, and sociocultural variables were evaluated using two different samples. The results showed that triadic family interactions were linked to preschoolers' attachment security levels in both groups, indicating the reliability of the proposed model.